Language in Web Communication: A Crash Course - How to raise the linguistic awareness of non-linguist professionals in the workplace - Toft, Birthe (Communication & Language at Work, 2012)
Having taught and carried out research in LSP and business communication for many years, I have come across, again and again, the problems arising from the inferior status of language in the business environment. Being convinced that it does not have to be so, instead of going on trying to convince non-linguistically trained colleagues of the importance of language via the usual arguments, I suggest that we let them experience the problems arising from the non-recognition of the importance of language via a Web communication crash course, inspired by a course taught to BA students at the University of Southern Denmark, Kolding.